Influence of the design parameters on the overall performance of a solar adsorption refrigerator. (February 2016) - Brites, G.J.V.N.; Costa, J.J.; Costa, V.A.F.
Abstract: This paper describes a parametric improvement study of a solar adsorption refrigerator, using a flat plate collector with silica-gel and water as the adsorption pair. Based on a set of experimental results obtained with a prototype, used mainly for model validation purposes, a numerical study is conducted to determine the influence of the most relevant parameters and to improve the overall performance. The main parameters considered in this study are: the mass of silica-gel, the number of metallic fins in the silica-gel bed, the orientation of the solar collector (azimuth angle), the improvement of the collector's cooling during the night, the thermal contact resistance between silica-gel and the collector plate, the condenser surface area, the evaporation surface area, the radiant properties of the collector plate, and the thermal insulation of the refrigerated cabinet. The influence of each individual parameter is analyzed, and its optimum value is determined. The refrigeration system with all the individually obtained optimum parameters has an overall performance considerably higher than that corresponding to the analyzed prototype, providing useful information for a better integrated understanding of the solar adsorption refrigeration systems, and for a better design of such systems looking for their maximum overall performance. Graphical abstract: Highlights: A solar refrigerator with adsorption cycle was built and tested in Portugal. Good experimental results but performance lower than expected. Parametric study to find the influence of selected parameters in the performance. A refrigerator with improved parameters was simulated, achieving high performance.